CORRELATION BETWEEN STUDENTS’ SELF-EFFICACY LEVEL AND THEIR SPEAKING ACHIEVEMENT - Yuliantari, Shinta; Femilia, Praptika Septi (Premise: Journal of English Education and Applied Linguistics, 2023)
English Educational students should have good or even high speaking ability because they are English teacher candidates who are expected to be able to speak English very well. They will speak English a lot when they become teachers later. If they have a low speaking ability, there might be a misunderstanding and them and their students. This study aims to determine if there is a positive correlation between the self-efficacy of English students and their speaking skills. The research utilized a correlational examination plan to examine the students' self-efficacy. The study used the self-efficacy Questionnaire and the speaking test for the 6th-semester English students of UIN KHAS. The sample size was composed of 137 students and used the Slovin formula. The sample total in this research is 34 consisting of 7 males and 27 females. Instrument Instruments for this research are a speaking test and a questionnaire. The information was examined using Statistical Package for Social Sciences (SPSS) 16.0 program. Researchers utilized the Pearson product-moment correlation to discover the correlation result. The correlation result is r count = 0.848, and the significance value is ρ = 0.000. The r table for N = 34 is 0.329. Therefore, the r count is more than the r table (0.848 > 0.329), indicating a strong correlation. In addition, the significance value is less than 0.05 (0.000 < 0.05). Therefore, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted.